(untitled) (Research, Society and Development, 2022)
Throughout history, evaluation has been marked by measuring the level of competence of a subject or function, with the objective of selecting a degree of superiority or inferiority. Therefore, we sought to identify and analyze the results of scientific productions related to evaluation. And answer the question: How does Assessment influence the teaching-learning process of the student and the teacher? The present research is an integrative review that proposes to analyze, describe and interpret the productions, in order to carry out a synthesis on the subject of evaluation. Through searches in the Scientific Electronic Library Online, using the descriptors: evaluation AND student OR Student AND teacher OR professor, and defining the inclusion and exclusion filters, the final result was 12 articles included. Based on the results, two thematic categories common to the studies were created. The first refers to determining the function of evaluation and the second determines which are the main focuses of study or trends in evaluations. It was found that evaluation is the main axis of pedagogical practice and only through it is it possible to improve the teaching process. Allowing the student to verify the teachings and indicating the thematic axes that are flawed, indicating improvement. For the teacher, it enables the correction of methodological mistakes and reflection on the learning process. Assessment is an instrument that aims to add to the formation of knowledge and, combined with continuous work in the classroom, enables the construction of the educational plan.